SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI R KLAME DENGAN MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Novri Adhiatma (JURNAL AKADEMIKA)
Installation of billboards is one of promotion strategy. Determination of the location of the installation of billboards, is one aspect that needs to be considered, both in terms of mounting billboards and from the Department of Housing Spatial Planning and the City of Edinburgh as the manager of installation of billboards. When determining the location of the billboard is not considered the area of the installation of billboards, so the information is to be conveyed from the billboard is not maximal. It therefore requires a system that can assist in the selection of the installation location of billboards. In making strategic location decisions billboard takes some parameters as assessment in determining the best location . Analytical Hierarchy Process ( AHP ) is a method that is used as a decision support . Placement of the billboard locations are based on 4 criteria: population density, the presence of educational facilities, office facilities and the existence of market presence. From each of these criteria will be performed mathematical calculations of the resulting solution to these problems so that the best alternative location